A Breath of Fresh Air: Raising Awareness for Clean Fuel Adoption - Farzana Afridi; Sisir Debnath; E. Somanathan (Institute of Labor Economics (IZA), 2020)
Air pollution is amongst the gravest public health concerns worldwide, and indoor sources are the largest contributors in many developing countries. In our study in central India, we randomly assign villages to a campaign by rural public health workers to either raise awareness about the adverse health effects of smoke from solid fuels and measures to mitigate them, or raise health awareness along with providing information on the universal cash-back LPG subsidy program or a control group in which neither information is provided. Using sales records of oil marketing companies, we find an over 6% increase in the purchase of LPG refills annually, almost 14% rise in monthly refill consumption and a 52% increase in self-reported induction stove usage in the combined treatment. There was no change in consumption of either LPG refills or usage of induction stoves in the health only treatment, but we observe behavioral changes - over 6 percentage points increase in the probability of the household having an outlet for smoke or a separate room for cooking. Our findings highlight the salience of financial constraints and the importance of the design of public subsidy schemes in inducing regular usage of clean fuels.
Keywords: D10; D90; I15; Q53; 330; air pollution; solid fuels; LPG; induction; health; subsidy; awareness; India